Multi-Disaster Susceptibility Analysis on The Majene-Mamuju National Road Section Using a Geographic Information System Approach - Awaluddin, Ahmad Reski; Afifah, Nur Zahrah; Basman, Ummu Kaltsum; Firmansyah; Fadliah, Nurul Awwalul (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2026)
The Trans-Sulawesi National Road section Majene-Mamuju (segment 010–009) is a vital land transportation artery supporting the mobility and economy of over 475,000 people. However, its geographical profile, narrow coastal corridors adjacent to steep hills and active fault lines, exposes it to severe multi-hazard threats. This study establishes a fixed infrastructure inventory of 94.7 km of national road and 79 critical bridge nodes to assess susceptibility to earthquakes, tsunamis, coastal abrasion, and landslides. Spatial analysis derived from sub-district data tables reveals that earthquakes are the most pervasive threat, impacting 90.69 km (95.8%) of the road and 65 bridges (82.3% of the inventory). Tsunami susceptibility represents the second most significant hazard, threatening 56.71 km (59.9%) of the network and 51 bridges (64.6%). Coastal abrasion affects 25.20 km (26.6%) of the road and 47 bridges (59.5%). Landslides, while localized, present a high-intensity risk to 5.66 km (6.0%) of the road and 6 bridges (7.6%). The Sendana, Tammeroddo Sendana, and Tubo Sendana sub-districts emerge as the most critical multi-hazard zones, with composite indices ranging from 2.57 to 2.82. While Ulumanda exhibits a high landslide susceptibility ratio (13.0%), Sendana represents the primary operational threat with 1.83 km of exposed road, nearly double the absolute physical impact found in Ulumanda. These findings provide a standardized scientific basis for prioritizing structural mitigation at critical bridge nodes to prevent total network severance during cascading disaster events.